Разложение обратной величины целой функции на простые дроби - Бакан, А.Г. (Видавничий дім "Академперіодика" НАН України, 2009)
Наведенi новi достатнi умови розкладностi на простi дроби оберненої величини цiлої функцiї однiєї комплексної змiнної. We give new sufficient conditions for the inverse quantity of an entire function of one complexvalued variable to be presented in the form of a series of primary fractions.